1982
DOI: 10.1063/1.443743
|View full text |Cite
|
Sign up to set email alerts
|

Positron lifetime studies on phase transitions of phospholipids

Abstract: Articles you may be interested inFlexibility of phospholipids with saturated and unsaturated chains studied by Raman scattering: The effect of cholesterol on dynamical and phase transitions Amorphous-amorphous transition in glassy polymers subjected to cold rolling studied by means of positron annihilation lifetime spectroscopy Positron-lifetime measurements have been made on the anhydrous crystalline form of DPPC (DL-adipalmitoylphosphatidylcholine) and on bilayer aggregates of 40% water-DPPC systems in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 9 publications
4
19
0
Order By: Relevance
“…This trend in lifetime agrees well with past studies [34][35][36]49 with a Dt oPs of 400 ps consistent with that reported by both McGrath et al 35 and Jean et al, 34 although the absolute lifetime values differ. Whilst these systems have previously been studied in the literature, interpretation and comparison of results is difficult, as the evolution of instrumentation and data analysis methods over the decades has made it difficult to directly compare the available data sets.…”
Section: Biomembrane Phase Transitions By Positron Annihilation Lifetsupporting
confidence: 92%
See 1 more Smart Citation
“…This trend in lifetime agrees well with past studies [34][35][36]49 with a Dt oPs of 400 ps consistent with that reported by both McGrath et al 35 and Jean et al, 34 although the absolute lifetime values differ. Whilst these systems have previously been studied in the literature, interpretation and comparison of results is difficult, as the evolution of instrumentation and data analysis methods over the decades has made it difficult to directly compare the available data sets.…”
Section: Biomembrane Phase Transitions By Positron Annihilation Lifetsupporting
confidence: 92%
“…This bound state is referred to as a ''positronium'' that may exist in two ground states, i.e. [31][32][33][34][35][36][37] However studies of this nature have been sparse, with many of the observations conflicting due to differences in data analysis and experimental design, so that it is difficult to extract physicochemically-meaningful comparative information from these studies. 12 oPs is of the greatest interest as the primary mechanism of annihilation is via ''pick-off'' with electrons in low electron density regions.…”
Section: Introductionmentioning
confidence: 99%
“…PALS is the only technique to gauge changes of local free volume voids in biomolecular systems. 25,26 We demonstrate that PALS measurements, complemented by DSC and atomistic molecular dynamics simulations, are able to characterize free volume changes caused by ceramides in the voids inside model membranes. The experimental results obtained in this work open the door for the study of free volume changes when different proteins or other molecules are present in cell membranes.…”
Section: Introductionmentioning
confidence: 90%
“…Some, such as Jean et al utilised concentrated bulk systems with reduced water content, 113 while others like McMahon et al measured dispersed systems in excess water. Some, such as Jean et al utilised concentrated bulk systems with reduced water content, 113 while others like McMahon et al measured dispersed systems in excess water.…”
Section: Pals: Influence Of Temperature and Chain Length On Membrane mentioning
confidence: 99%